Antioxidant Activity of TEMON (Clitoria ternatea and Citrus sp.) as an Infused Herbal Tea - Wahyu Widowati; Teresa Liliana Wargasetia; Teddy Markus Zakaria; Meganita Marthania; Ria Aprilia Tri Puteri Permata Akbar; Michael Sebastian Gunadi; Nathanael Halim; Sherly Santiadi (Faculty of Pharmacy, Universitas Gadjah Mada, 2022)
Many people around the world believed that herbal tea had a lot of antioxidants contained in it, thus it was widely drunk all over the world. However, the antioxidant capacities of herbal tea may be various because it is affected by the usage of different plants as its primary ingredient. As a result, this study examines the antioxidant activity of herbal tea made from dried Citrus sp. and Clitoria ternatea flower petals. The antioxidant potential was assessed by performing a DPPH and H2O2 scavenging activity assay on 2,2-diphenyl-1picrylhydrazyl (DPPH) and hydrogen peroxide (H2O2) scavenging activity assay, total phenolic, and flavonoid content assay, ABTS reduction, and FRAP assay. This study showed that pure telang (Clitoria ternatea) herbal tea has antioxidant properties. Dried Telang (Clitoria ternatea) tea had the highest activity of antioxidants as we refer to the results of it had the highest activity value in DPPH, ABTS, and FRAP assay and also had the lowest IC-50 value. Followed by TEMON infusion which showed the second-highest antioxidant activity after pure telang infusion. The decrease in antioxidant activity in the mixture of telang and lemon was due to the mixture of lemons which tended to have the lowest antioxidant activity among the three types of infusions tested. The addition of dried lemon has the aim of enhancing the flavor of the tea infusion.